AN EXTENSION OF SOME RESULTS DUE TO JARDEN - Shannona, Anthony G.; Cook, Charles K.; Hillman, Rebecca A. (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
This paper defines some generalized Fibonacci and Lucas sequences which satisfy arbitrary order linear recurrence relations and which answer a problem posed by Jarden in 1966 about generalizing an elegant result for a connection between even and odd subscripted Fibonacci and Lucas numbers.